2019
DOI: 10.1186/s13075-018-1803-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D protects podocytes from autoantibodies induced injury in lupus nephritis by reducing aberrant autophagy

Abstract: SubjectThe aim of this study was to investigate whether vitamin D plays a protective role in podocyte injury induced by autoantibodies purified from the serum of patients with lupus nephritis (LN) via reducing aberrant autophagy.MethodsAutophagic activities of renal tissues of patients with LN were evaluated under transmission electronic microscope (TEM). Immunoglobulin G (IgG) from patients with LN was purified to induce human podocyte injury, and the role of vitamin D in injury was observed. Podocytes were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…For example, in patients with diabetes (Wu et al, 2018;Zhao et al, 2018;Li et al, 2020) and IgA nephropathy (Liang et al, 2018), decreased podocyte autophagy activity is observed; while in systemic lupus erythematosus (SLE) (Jin et al, 2018) or adriamycin-induced models of nephrotic syndrome (Yu et al, 2018), podocyte autophagy activity is found to be increased. Yu et al (2019) observed an increase in the number of autophagosomes and the expression of autophagy-related proteins such as LC3B-II and Beclin-1 in podocytes stimulated by lupus autoantibodies. In the present study, the expression of LC3-II and the number of autophagosomes decreased after H 2 O 2 treatment, suggesting that the formation of autophagosomes was blocked.…”
Section: Discussionmentioning
confidence: 85%
“…For example, in patients with diabetes (Wu et al, 2018;Zhao et al, 2018;Li et al, 2020) and IgA nephropathy (Liang et al, 2018), decreased podocyte autophagy activity is observed; while in systemic lupus erythematosus (SLE) (Jin et al, 2018) or adriamycin-induced models of nephrotic syndrome (Yu et al, 2018), podocyte autophagy activity is found to be increased. Yu et al (2019) observed an increase in the number of autophagosomes and the expression of autophagy-related proteins such as LC3B-II and Beclin-1 in podocytes stimulated by lupus autoantibodies. In the present study, the expression of LC3-II and the number of autophagosomes decreased after H 2 O 2 treatment, suggesting that the formation of autophagosomes was blocked.…”
Section: Discussionmentioning
confidence: 85%
“…Thus, we evaluated the number of autophagic vacuoles alone. The appearance of autophagy should be further investigated in other forms of human glomerular diseases, including lupus nephritis [45] and diabetic nephropathy [26]. The mechanism of interaction between autophagy and FPE in podocytes is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of vitamin D deficiency on the development of SLE, Yu et al ( 141 ) recently demonstrated that vitamin D plays a protective role in the autoantibody-induced injury of podocytes (kidney cells that wrap around capillaries of the glomerulus) in patients with lupus nephritis, which could be a potential novel therapeutic target to treat lupus nephritis. From a 24 week double-blind randomized placebo-controlled trial by Lima et al ( 142 ), it was established that supplementation of vitamin D in patients with juvenile-onset SLE effectively improved parameters of bone microarchitecture ( p = 0.024).…”
Section: Micronutrientsmentioning
confidence: 99%